2022
DOI: 10.1177/00048674221085923
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle risk factors for obsessive-compulsive symptoms and related phenomena: What should lifestyle interventions target?

Abstract: Objective: Understanding the impact of lifestyle on mental illness symptoms is important for informing psycho-education and developing interventions which target mental and physical comorbidities. Obsessive-compulsive and related disorders can have a significant impact on health-related quality of life and physical health. However, our understanding of the impact of lifestyle on obsessive-compulsive symptoms and broader compulsive and impulsive problematic repetitive behaviours is limited. Aims: We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…More severe OCD symptoms were associated with unhealthier dietary habits, higher tobacco use, fewer hours of sleep, and a non-restorative sleep. This is partly in line with previous research findings showing a significant association between higher obsessive-compulsive symptom severity and lower intake of vegetables and oily fish [ 76 ]. These results contrast with those reported by Nguyen et al [ 24 ], who found no association between OCD severity and dietary quality.…”
Section: Discussionsupporting
confidence: 93%
“…More severe OCD symptoms were associated with unhealthier dietary habits, higher tobacco use, fewer hours of sleep, and a non-restorative sleep. This is partly in line with previous research findings showing a significant association between higher obsessive-compulsive symptom severity and lower intake of vegetables and oily fish [ 76 ]. These results contrast with those reported by Nguyen et al [ 24 ], who found no association between OCD severity and dietary quality.…”
Section: Discussionsupporting
confidence: 93%
“…Another helpful attempt is lifestyle intervention. Potential intervention targets supported by current research evidence are developing anti-inflammatory diets and increasing physical activity [ 98 ]. Other researchers have suggested that interventions should focus on reducing stress and improving sleep quality [ 19 ].…”
Section: Primary Secondary and Tertiary Prevention Of Pediatric Ocdmentioning
confidence: 99%